2019
DOI: 10.2135/cropsci2019.06.0367
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Genetic Diversity of Wild Cranberry Populations in the Upper Midwestern United States

Abstract: P lant breeding is crucial for food production and food security; however, multiple cycles of selection can result in the loss of genetic diversity (Cheema, 2018). This genetic diversity loss leads to crop homogeneity, which makes food systems vulnerable to biotic and abiotic stresses, as has been the case of many crops, such as bananas (Musa acuminata Colla, M. balbisiana Colla) and potatoes (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 63 publications
1
8
0
Order By: Relevance
“…Clear separation between the two species has been previously observed using amplified fragment length polymorphism (AFLP) [34] and SSR markers [22]. Rodriguez-Bonilla et al [23] also observed a clear differentiation between species collected in natural areas in the states of Wisconsin and Minnesota, demonstrating the ability of these markers to differentiate between closely related species. 2), which are comparable to those found by Zalapa et al [22] and Rodriguez-Bonilla et al [23], who found high levels of heterozygosity in wild populations in both Wisconsin and Minnesota.…”
Section: Genetic Analysis Shows High Differentiation Between Morphologically Similar Speciesmentioning
confidence: 75%
See 1 more Smart Citation
“…Clear separation between the two species has been previously observed using amplified fragment length polymorphism (AFLP) [34] and SSR markers [22]. Rodriguez-Bonilla et al [23] also observed a clear differentiation between species collected in natural areas in the states of Wisconsin and Minnesota, demonstrating the ability of these markers to differentiate between closely related species. 2), which are comparable to those found by Zalapa et al [22] and Rodriguez-Bonilla et al [23], who found high levels of heterozygosity in wild populations in both Wisconsin and Minnesota.…”
Section: Genetic Analysis Shows High Differentiation Between Morphologically Similar Speciesmentioning
confidence: 75%
“…Molecular markers such as simple sequence repeats (SSR) have been identified for many plant species and successfully used to gain insights into the genetic diversity of CWR of several crops, including apple [18], wheat [19], sugarcane [20], and sweet potato [21]. In cranberry, SSR markers have been used to evaluate the genetic diversity of wild populations in Wisconsin and Minnesota [22,23] and have proven to be transferable across species in the genus Vaccinium [24], which will also facilitate interspecific breeding and fingerprinting. Results from genetic diversity analyses have provided sufficient information to aid in situ conservation efforts in several plant species, such as Borderea chouardii Gaussen and Heslot, an endangered plant in Spain [25], and wild potatoes in Argentina [26].…”
Section: Introductionmentioning
confidence: 99%
“…The analyses presented are strongly supported by genome-wide sequence variation revealed by more than 21,000 SNPs, the largest set of markers ever used in cranberry (Figure 1). Compared to previous diversity studies in cranberry (Fajardo et al, 2013;Zalapa et al, 2015;Schlautman et al, 2017a;Schlautman et al, 2018;Rodríguez-Bonilla et al, 2019), both the number of accessions examined and the number of genetic markers are greatly increased.…”
Section: Discussionmentioning
confidence: 99%
“…Cranberry genetics studies that have contributed to the ongoing development of markerbreeding strategies include a genome assembly (Polashock et al, 2014), several high-density linkage maps (Schlautman et al, 2015;Covarrubias-Pazaran et al, 2016;Schlautman et al, 2017a), QTL mapping of fruit rot resistance (Georgi et al, 2013;Daverdin et al, 2017), fruit size and shape (Diaz-Garcia et al, 2018a), and fruit metabolites (Diaz-Garcia et al, 2018b;Fong et al, 2020), and genomic selection studies (Covarrubias-Pazaran et al, 2018). Additionally, only a few studies have investigated the genetic diversity in cranberry cultivars, cranberry wild populations, and native populations (Fajardo et al, 2013;Zalapa et al, 2015;Schlautman et al, 2017b;Schlautman et al, 2018;Rodríguez-Bonilla et al, 2019), most of them based on a limited number of genetic markers.…”
Section: Introductionmentioning
confidence: 99%
“…Three papers focused on specific crops such as carrots, lettuce and cranberry provide an important speciesspecific approach to plant conservation (Mezghani et al, 2019;Lebeda et al, 2019;Rodríguez-Bonilla et al, 2019). A crop-specific approach can highlight conservation priorities as well as persisting gaps in species-specific knowledge of taxonomy, crossability, distribution and trait characterizations.…”
Section: Why Connect Agriculture Public Gardens and Science?mentioning
confidence: 99%